The Rise of Telecities: Decentralizing the Global Society. - Pelton, Joseph N. (Futurist)
The creation of telecities are a solution to reverse the trend toward megacities. Megacities put massive numbers of people at risk for terrorist attacks and natural disasters—something that leaders and planners are only slowly realizing. These cities will be superseded by telecities due to the drive toward clean air, cutting pollution, energy conservation, more jobs based on services, and dealing with the high cost of urban property. Moreover, information available to the global society is accelerating at exponential speeds today, with electronic networks and satellites linking even the most remote areas. Global information networks are now generating truly global corporations, supporting electronic immigrants, and fostering telework and telecommuting for tens of millions of workers worldwide.